The Effectiveness Application of ESL-LAB as A Media to Improve Students’ Listening Skill - Amalia, Nizma Efriza; Rohiyatussakinah, Ina; Hendra, Hendra (Program Studi Magister Tadris Bahasa Inggris UIN Sultan Maulana Hasanuddin Banten, 2026)
This study aimed to determine the effect of ESL-LAB as media to improve student’s listening skill. This research conducted at SMKN 3 Kota Serang. Quasi-experiment with non-equivalent pre-test post-test design was applied in this research. The results of the study were evidenced by the N-Gain results of the experimental class which increased compared to the control class. The first the Paired Samples T-test aim to see that there was a significant effect of the ESL-LAB application as a media to improve students' listening skill. The result was <0.001, meaning that ?0 rejected and ?? accepted, which means that there was a significant effect of the ESL-LAB application as a media to improve students' listening skill. In the second hypothesis using the Independent Samples T-test which states that the sig value in this study was <0.001 which indicates that ?0 rejected and ?? accepted which means that there were differences in the use of ESL-LAB as a media to improve students' listening skill. It could be concluded that the use of ESL-LAB could improve students' listening skill after using ESL-LAB and there was a significant effect on tenth grade at SMKN 3 Kota Serang.